Analysis of Community Health Center Performance on Tuberculosis Control Programs - Essenzi, Desma Sekar (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To explore and analyze the implementation of the Tuberculosis control program using the DOTS strategy at the Satelit Community Health Center. This research aims to identify factors that support and hinder the implementation of the program, evaluate the effectiveness of approaches that integrate Islamic values ​​in health education. Methodology: This research uses a qualitative method with a case study design. The population in this study were all individuals involved in the TB control program at the Satellite Health Center. The data collection technique in this research uses in-depth interviews with guided questions that have been prepared in advance. Data obtained from interviews were then analyzed using thematic analysis method. Main Findings: This research shows that the implementation of the Tuberculosis control program at the Satelit Community Health Center has gone well even though it still faces various challenges. The success of the program is greatly influenced by political commitment, the performance of the Medication Monitor (PMO), as well as adequate facilities and training support. The integration of Islamic values in health education has proven effective in increasing patient compliance and community participation. Novelty/Originality of this study: The novelty of this research lies in the holistic approach in evaluating the performance of community health centers in managing TB, which includes the use of information technology to improve data recording and reporting, intensive training for medical staff in TB case management, as well as improving the infrastructure of community health centers to support more efficient services.